Spjallmennis ráðgjafi - Íba - Diemut Haberbusch 1979-; Helga Rún Steinarsdóttir 1993-; Laura Orsini Ribeiro Franca 1987- (2019)
Spjallmennisráðgjafinn Íba is a final project in BSc in Computer Science at University of Reykjavík, done in cooperation with Íslandsbankinn. Íba is a text based conversational chatbot, created to aid customer service by answering common queries (such as currency exchange rates, opening hours, and location of branches). Íba aims to expedite service time for both bank users as well as customer service employees. The researchers conducted surveys to gather data about the viability of such a bot, which is entirely trained in the Icelandic language.